Economic vulnerability and resilience concepts and measurements - Lino Briguglio; Gordon Cordina; Nadia Farrugia; Stephanie Vella (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In this paper, economic vulnerability is defined as the exposure of an economy to exogenous shocks, arising out of economic openness, while economic resilience is defined as the policy-induced ability of an economy to withstand or recover from the effects of such shocks. The paper briefly reviews the work already carried out on economic vulnerability and extends the research towards the development of a conceptual and methodological framework for the definition and measurement of economic resilience. Towards this end, the paper proposes an index of economic resilience gauging the adequacy of policy in four broad areas, namely macroeconomic stability, microeconomic market efficiency, good governance and social development.
Keywords: 330; economic vulnerability; economic resilience; small states